(untitled) (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2009)
New monomeric Cu(II) complex of 5-(2-pyridyl)-4H-1,2,4-triazole-α-ylacetic acid ethyl ester (L) have been prepared. Obtained compound were studied by means of ESR- and IR-spectroscopy. The molecular and crystal structure of Cu(L)Cl2 have been studied by the single crystal X-ray diffraction. Square-planar [CuN2Cl2] coordination configuration was found and are suggested to be due to the helating nature of the ligand, which interacts with Cu(II) through N2triazole and Npyridine atoms. As an interesting peculiarity of the molecular structure of Cu(L)Cl2, one should note the strong intramolecular hydrogen bond between triazole hydrogen and oxygen of ester group.